Factors Affecting the Determination of Minimum Wages for the People of Binjai City - Harahap, Eko Aulia; Herlina, Sri (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2025)
This research discusses the City Minimum Wage which is the minimum standard for employers in determining employee salaries in Binjai. This study aims to determine the significant effect of the Gross Regional Domestic Product (X1) and Labor Force Participation Rate (X2) variables on the City Minimum Wage (Y) in East Binjai District. The type of research used is associative research, which aims to see the relationship between the independent variable and the dependent variable. The data used is quantitative data, and the data source is secondary data with data collection techniques through literature studies and documentation. The analytical tools used include the Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test. The results showed that there was no significant influence between Gross Regional Domestic Product (X1) and Labor Force Participation Rate (X2) on the City Minimum Wage (Y) in Binjai, East Binjai District.